NEW UZBEKISTAN - NEW CONSTITUTION! - Abdurazakova Kamolakhan Yusupovna (Journals Park Publishing, 2024)
This article talks about the new constitution in the new Uzbekistan.
Keywords: republic, law, department, changes.